Internalization of Islamic Values Through Tartil Reading of the Qur’an in a Psychological Perspective at Al-Yasini Pasuruan Integrated Islamic Boarding School - Arofatul Muawanah (Proceeding International Conference on Religion, Science and Education, 2023)
The command to read the Qur’an tartly is mentioned by Allah in QS al Muzammil verse 4. In the process, reading the Qur’an tartly allows for the process of internalizing Islamic values, especially for students who are domiciled at the Al Yasini Islamic Boarding School, Pasuruan, East Java. In addition, reading the Qur’an with the tartil method has various benefits, especially from a psychological point of view. Therefore this study aims to (1) find out the internalization of Islamic values through reading the Qur’an tartil at the Al-Yasini Integrated Islamic Boarding School; (2) know how to read the Koran tartil in a psychological review at the Al Yasini Integrated Islamic Boarding School. This research is a qualitative research. Sampling was carried out by purposive sampling which limited the sources to female students, namely students who also studied at STAI al-Yasini Pasuruan. Data collection was carried out through interviews, observation and documentation techniques. The results are that (1) the process of internalizing Islamic values through reading the Qur’an tartil at the Al Yasini Integrated Islamic Boarding School occurs through three stages, namely the stage of value transformation occurs when the kyai recites certain verses tartil; the value transaction stage when there is two-way communication between the kyai and the santri; the stage of transinternalization of values that focuses on the personality and morals of the kyai who are role models for the santri; (2) reading the Qur’an tartil in a psychological perspective has a variety of benefits, including helping to focus attention, being able to raise questions, opening material for discussion, tending to have a critical attitude towards the verses being read so as to bridge the reader’s deep understanding and contemplation verse content, improve one’s linguistic intelligence, etc.